A Study about Prevent Tampering with Encrypted Messages over the Network Using Digital Signature. (9th July 2022) - Al-khairow, Majed; Al-halabi, Mohamad Firas
Abstract : In this paper, we present a proposed model to increase the authenticity of messages sent over the network; our model went through two stages: First, It is the modification of the MD5 algorithm, which is the basic and comprehensive algorithm from which the Digital signature was launched, where we have modified the logical operations by changing the direction of the shift from left to right and by changing the order of the temporary storage spaces (a, b, c, d). We came up with a lower execution time, and we also compared the execution time of our modified algorithm with the original algorithm and some other Digital signature algorithms. Second, the integration of our modified algorithm with cipher algorithms to increase the authenticity of the sent messages. We applied an example to our proposed model where we used two encryption standards (AES, DES). Finally, we implemented the model using the C# programming language.